Metallic Taste Phantom Predicts Oral Pain among 5-year Survivors of Head and Neck Cancer - Logan, Henrietta L. (2008)
Chronic pain following cancer-related treatment is emerging as a major concern. Heretofore, the pain level among 5-year survivors of head and neck cancer has received limited attention. This study proposes a predictive model for understanding factors associated with elevated levels of chronic oral pain. Cancer survivors were drawn from a pool of 5-year survivors. A listed sample matched on sex, age, and zip code was purchased and served as a comparison group. Telephone interviews were conducted by a professional call center. Oral pain levels and the presence of metallic taste phantoms were significantly higher in the cancer survivor group than among the comparison group. The prevalence of chronic oral pain among the 5-year survivors was 43% compared to 13% for the comparison group. Hierarchical linear regression showed that among the 5-year survivors, the predictive model for spontaneous pain accounted for 24% of the variance, and for function-related pain the model accounted for 34% of the variance, with the presence of a phantom metallic taste making a significant independent contribution in both models. In the function-related pain model, depression and level of oral function quality of life (QOL) made significant independent contributions. The presence of oral pain is a significant problem among head and neck cancer survivors. The presence of metallic phantoms is an important new piece of evidence suggesting neural damage following cancer-directed treatment. Routine assessment of oral pain levels could improve current analgesic approaches among head and neck cancer survivors.